Systematic Reversed-Phase Liquid Chromatography Method Development for Pharmaceutical Degradation: A study on Mometasone Furoate - Nilsson,Nicole (2025)
HPLC is one of the most widely used analytical techniques in the pharmaceutical industry used for separation and identification of compounds in complex formulations. Despite its advantages, HPLC method development remains challenging. This is due to the need to optimize multiple interdependent parameters simultaneously, while gaining high precision, reproducibility, and efficiency. Even minor changes to a single parameter can significantly impact the entire outcome, making the process complex. More traditional HPLC method development approaches, such as trial-and-error, are inefficient and often lacks reproducibility. While pharmacopeial methods provide a good foundation for analysis, they are not always suitable for samples with increased complexity arising from sources of impurities and degradation products, showcasing the need for systematic optimization strategies. The aim of this work is to develop and optimize a systematic HPLC method development using experimental design principles to improve resolution of present chemical substances, robustness of the method, and separation efficiency in pharmaceutical analysis. The study follows a four-phase approach: screening of different columns including different stationary phase chemistries and column dimensions, screening of eluent conditions, optimization using iterative testing, and lastly, robustness testing to evaluate sensitivity to minor variations. A skin-cream formulation with the active drug mometasone furoate, which is a neutral and hydrophobic compound, including common impurities and degradation products, was used as a model sample for the study. Screening of four different stationary phases using RP-HPLC identified Super C18 and Super Phenyl Hexyl columns to be better fitted for further testing due to improved impurity resolution. Four different particle sizes with similar dimensions were also tested, where 3 µm particles yielded the best efficiency and peak shapes. Out of six different injection volumes, 8 µL gave optimal peak symmetry. Mobile phase optimization with linear gradients of twelve different compositions found that combinations involving water, acetonitrile, and either THF or methanol gave the highest theoretical plate counts and resolution. Method validation showed better precision and reproducibility with the water-acetonitrile-methanol system, although complete resolution of all impurities was not achieved. Systematic method development using experimental design improved chromatographic efficiency and robustness, enhancing impurity resolution for mometasone furoate. While fully improved impurity resolution was not completed during this time span, the developed method and optimization plan offer a structured approach to improve reproducibility and efficiency in pharmaceutical quality control.
Keywords: HPLC; Chromatography; Analytical method; Pharmaceutical analysis; Method development; Analytical chemistry